2016
DOI: 10.5513/jcea01/17.4.1838
|View full text |Cite
|
Sign up to set email alerts
|

Blood plasma levels of anterior pituitary hormones of rabbits after apricot seed exposure in vivo

Abstract: The present study describes possible changes in plasma levels of anterior pituitary hormones induced by bitter apricot (Prunus armeniaca L.) seeds in young female rabbits in vivo. Prunus armeniaca L. is an important medicinal edible plant species commonly known as "apricot". The apricot is a member of the Rosaceae and subfamily Prunoideae. It is one of the most delicious and commercially traded fruits in the world. Apricot kernel is the inner part of the seed of the apricot fruit. The kernel is used to produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…It has possible modulatory impact on cell viability [25] and the steroid production in porcine ovaries in vitro, as Halenár et al [26,27] reported in their study. Michalcová et al [28] published, that natural substances present in apricot seeds may be involved in ovarian folliculogenesis mechanisms of rabbits through inhibition of FSH (follicle-stimulating hormone) levels. Amygdalin is also a potential antifibrotic agent that may have therapeutic potential for patients with fibrotic kidney disease [29].…”
Section: Resultsmentioning
confidence: 99%
“…It has possible modulatory impact on cell viability [25] and the steroid production in porcine ovaries in vitro, as Halenár et al [26,27] reported in their study. Michalcová et al [28] published, that natural substances present in apricot seeds may be involved in ovarian folliculogenesis mechanisms of rabbits through inhibition of FSH (follicle-stimulating hormone) levels. Amygdalin is also a potential antifibrotic agent that may have therapeutic potential for patients with fibrotic kidney disease [29].…”
Section: Resultsmentioning
confidence: 99%
“…Amygdalin is the major component of apple seeds, which contains 2,96 mg/g of amygdalin. Of course there are differences between amounts of amygdalin in seeds depending on cultivars (Michalcová, et al, 2016). Apple juice (100% pressed) contain 0,09mg/g of amygdalin, so it is much lower than observed in apple seeds.…”
Section: Amygdalinmentioning
confidence: 92%
“…Apricot kernel paste can heal vaginal infections. The kernel oil has been used in cosmetics and as a pharmaceutical agent (laxative and expectorant) (14).…”
Section: Introductionmentioning
confidence: 99%